2015
DOI: 10.1111/pedi.12285
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of insulin pump settings in children and adolescents with type 1 diabetes mellitus

Abstract: AimTo characterise current insulin pump settings used in young patients with type 1 diabetes mellitus (T1DM) and their relationship to glycaemic and weight control. MethodsThis retrospective study included patients aged <18 years old with T1DM duration >1 year who were using the Medtronic pump device. Data from the insulin pumps including number of blood glucose (BG) tests per day, basal and bolus insulin parameters, carbohydrate ratio (CR) and insulin sensitivity factors (ISF) were averaged over 14 days for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 27 publications
2
32
0
2
Order By: Relevance
“…This study found that bolus insulin requirements estimated by the 500 rule were lower than the actual bolus doses used by the study participants. These results confirmed the findings of other studies, which demonstrated that the 500 rule underestimated the insulin requirements for children and adolescents with T1DM …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study found that bolus insulin requirements estimated by the 500 rule were lower than the actual bolus doses used by the study participants. These results confirmed the findings of other studies, which demonstrated that the 500 rule underestimated the insulin requirements for children and adolescents with T1DM …”
Section: Discussionsupporting
confidence: 91%
“…Some studies conducted on children with T1DM demonstrated that ICR had diurnal variation with higher bolus insulin requirement at morning meal than for other meals . Although this diurnal variation in ICR was not found in other studies, it is essential to assess the ICR for each meal separately.…”
Section: Introductionmentioning
confidence: 92%
“…Pump therapy for type 1 diabetes (T1D) offers theoretical advantages over multiple daily insulin injection regimens, such as improved glycemic control, reduced hypoglycemia, and increased lifestyle flexibility. However, most people using pumps do not frequently re‐evaluate and adjust insulin dose settings necessary for optimal management of T1D . This may explain why diabetes outcomes are similar in those using pump therapy and multiple daily insulin injection regimens .…”
mentioning
confidence: 99%
“…5 Young children are also more insulin sensitive, with lower total daily insulin needs per body weight. 6 Therefore, it is not surprising that children under 6 years of age are about 2.5 times more likely than older children to have hypoglycemic events. 7 Beyond these considerations, shortcomings in the accuracy of syringes and insulin pen devices at small insulin doses have long been recognized.…”
mentioning
confidence: 99%
“…11 The availability of insulin pens with half-unit increments has added some flexibility for younger children, but it does not address the minimum dose problem. 12,13 Because 0.5 units of U100 insulin may decrease the blood glucose of a typical 2 year old by 150 mg/dL (8.3 mmol/L), 6 even the smallest available insulin pen dose forces the user to tolerate blood glucose levels well above target range before being able to give a correction dose. For this reason, insulin pumps that allow mimimum doses and dose increments of 0.025-0.1 units have become an increasingly favored therapy for the youngest children, and outcomes studies have shown lowered risk of hypoglycemia with comparable or improved HbA1c levels and no increase of diabetic ketoacidosis risk in this age group.…”
mentioning
confidence: 99%